An Overview of Saturable Inductors: Applications to Power Supplies - Kaiser, Jeremias; Dürbaum, Thomas (IEEE Transactions on Power Electronics, 2021)
This paper presents an overview of saturable inductors that are intentionally saturated by the load current and their applications to power supplies. After introducing the fundamentals of magnetization and non-linear inductance, three types of saturable inductors are differentiated. They are based on the way non-linearity of the core material is used. The partial saturation, the saturation of swinging inductors and the full saturation. Subsequently, the paper focuses on the application to power supplies: it identifies the main reasons for using saturable inductors, like improving the efficiency or reducing the size of the magnetic component by using stepped air-gaps or partial saturation and gives an overview on this topic and its main publications. Afterwards some concepts and circuits taking advantage of saturable inductors are presented in more detail, especially improving the light load efficiency of a point of load (PoL) buck converter, ensuring zero voltage switching (ZVS) over a wide load range in a phase-shifted full bridge (PSFB) circuit, a nonlinear commutation circuit and a passive and active power factor correction (PFC).
CRIS-Team Scopus Importer:2021-03-19
Keywords: Ferrites; Inductance; Inductors; Magnetic cores; Magnetic hysteresis; Permeability; Saturation magnetization